2021
DOI: 10.32598/jpr.9.2.930.1
|View full text |Cite
|
Sign up to set email alerts
|

Parental Factors Affecting the Incidence of Infantile Colic: A Systematic Review

Abstract: Context: Infantile Colic (IC) is an essential problem in infancy that is influenced by factors related to infants and parents. The parental factors associated with colic have not been comprehensively assessed. Objectives: The present systematic review was conducted to investigate the parental factors affecting the incidence of IC. Data Sources: Databases, including PubMed, Web of Science, Scopus, Science Direct, Google scholar, as well as Scientific Information Database (SID), and Magiran (Iranian websites) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(63 reference statements)
1
0
0
1
Order By: Relevance
“…Similarly, a family history of migraines was significantly more common in infants with colic. These outcomes align with the systematic review by Firooz et al, which identified maternal history of migraine as a key predisposing factor for infantile colic (32). Abbasi et al explored the link between infantile colic and parental migraines in infants aged 4 to 12 weeks, finding that histories of parental (either father or mother) and specifically maternal migraines were significantly more prevalent in infants with colic, echoing the results of our study (33).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, a family history of migraines was significantly more common in infants with colic. These outcomes align with the systematic review by Firooz et al, which identified maternal history of migraine as a key predisposing factor for infantile colic (32). Abbasi et al explored the link between infantile colic and parental migraines in infants aged 4 to 12 weeks, finding that histories of parental (either father or mother) and specifically maternal migraines were significantly more prevalent in infants with colic, echoing the results of our study (33).…”
Section: Discussionsupporting
confidence: 90%
“…Unido a estos componentes conductuales, Gordon y col. 16 no descartan la posibilidad de tener en cuenta factores biológicos que contribuyan a su manifestación, como la hipersensibilidad y/o alergia a los alimentos, la microflora y la dismotilidad intestinal. Con relación a los componentes psicológicos, Firooz y col. 17 en una revisión sistemática realizada en diciembre del 2019, identificaron factores parentales que afectan la incidencia de CI. Al analizar 18 trabajos de investigación (10 estudios prospectivos, 6 transversales y 2 de casos y controles) encontraron que la depresión de los padres, la ansiedad y el bajo apoyo familiar inciden en la incidencia de CI, proponiendo que la identificación de estos factores de riesgo y la planificación precisa pueden ser beneficiosas en la prevención y el tratamiento del CI.…”
Section: Discussionunclassified